Braided silicone rubber membranes for organic extraction from aqueous solutions: II. Application to contained liquid membranes - Cocchini,U; Nicolella,C; Livingston,AG (Journal of Membrane Science, 2002)
Aqueous-aqueous extraction experiments were performed in a double tube mass exchanger (DTMEx) in order to investigate mass transfer characteristics of steel-braided non-porous membranes in a contained liquid membrane (CLM) module. Toluene was the permeating molecule, polydimethylsiloxane (PDMS) and ethylene propylene diene monomer (EPDM), were used as non-porous membrane materials, and silicone oil and polypropylene glycol (PPG) as liquid membranes. The liquid membrane contribution to the overall mass transfer resistance was assessed for different module configurations (e.g. varying membrane separation distance) and operating modes (e.g. stationary and mobile liquid membrane). The liquid membrane was found to be the dominant resistance when the module was operated with a stationary liquid membrane, a large separation distance between the braided membranes, and non-porous membranes with high affinity for the permeating molecules. When the liquid membrane was circulated through the module this resistance became negligible compared to the cumulative resistances in the aqueous hydrodynamic boundary layers (HBLs) and membrane at the feed and extractive side, resulting in overall mass transfer coefficients (OMTCs) up to 2.7×10-5ms-1. CLMs with braided membranes and mobile liquid membrane may therefore be advantageously used for aqueous-aqueous separation of hydrophobic molecules in modules operating with high liquid velocity in the membrane tubes. © 2002 Elsevier Science B.V. All rights reserved.